Urgensi Metodologi dalam Sejarah Keilmuan: Sebuah Pengalaman Lampau Tradisi Ilmiah Islam - Anwar Nuris (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2019)
AbstractIslam as a civilization has make a full picture about the methodological process of Islamic studies. That process have confirm how important a methodology in basic making of islamic civilization. The methodology can make a new perspective in theory formulization. This is very important, remembering the methodological tradition in classical islamic treasury has a long history and regarded as foundation in islamic basics intellectual. Of course, if not the formulation, the principle and spirit usually have the meaning in living today. Keywords : Scientific, Islam, Tradition